2018
DOI: 10.1111/ene.13625
|View full text |Cite
|
Sign up to set email alerts
|

A novel heterozygous variant in ERLIN2 causes autosomal dominant pure hereditary spastic paraplegia

Abstract: Biallelic variants in ERLIN2 are known to cause recessive HSP type SPG18. Here, the first two families with an autosomal dominant, pure form of HSP caused by a novel ERLIN2 heterozygous missense variant are described. These findings expand the mutational and inheritance spectrum of SPG18. ERLIN2 variants should also be considered in the diagnostic evaluation of patients with autosomal dominant HSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…The vast majority of previous studies of ERLIN2 ‐related disorders have identified biallelic variants (Table S2). One report, however, identified a recurrent heterozygous missense variant (c.386G> C; p.Ser129Thr) in multiple affected individuals from two large unrelated families . Overall, these data lend support to the notion that there are autosomal‐recessive and autosomal‐dominant forms of ERLIN2 ‐related disorders, similar to a small number of other genetic causes of HSP, such as defects in ATL1 (SPG3A), KIF1A (SPG30), KIF1C (SPG58), REEP1 (SPG31), and SPG7 (SPG7) …”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The vast majority of previous studies of ERLIN2 ‐related disorders have identified biallelic variants (Table S2). One report, however, identified a recurrent heterozygous missense variant (c.386G> C; p.Ser129Thr) in multiple affected individuals from two large unrelated families . Overall, these data lend support to the notion that there are autosomal‐recessive and autosomal‐dominant forms of ERLIN2 ‐related disorders, similar to a small number of other genetic causes of HSP, such as defects in ATL1 (SPG3A), KIF1A (SPG30), KIF1C (SPG58), REEP1 (SPG31), and SPG7 (SPG7) …”
Section: Discussionsupporting
confidence: 52%
“…The patient with the de novo heterozygous ERLIN2 variant (patient 5) appeared less severely affected compared to the other participants with homozygous ERLIN2 variants, as was shown by a later age of symptom onset, absence of developmental regression, and absence of ID. In fact, among prior reports of ERLIN2 ‐related disorders (Table 2), ID was absent in 5/6 unrelated individuals who had a missense ERLIN2 variant on at least one allele (three families with affected individuals); conversely, ID was present in all individuals with a homozygous truncating variant . This observation suggests that ERLIN2 ‐related disorders can present dosage‐dependent clinical features likely due to reduced protein function.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Interestingly, mutations to erlin1 and, more commonly, erlin2 have been linked to rare neurodegenerative diseases; e.g. hereditary spastic paraplegia (7,(19)(20)(21)(22)(23)(24)(25)(26)(27). As yet, however, it has not been possible to define how the mutations affect the cell biological function of erlin2, or the erlin1/2 complex, and cause cell dysfunction (7).…”
Section: +mentioning
confidence: 99%
“…Family members highlighted in pink may benefit from cascade testing. 51 . The variant was also detected in his daughter (40s), currently without clinical manifestations.…”
Section: Medically Significant Genetic Findingsmentioning
confidence: 99%